2000
DOI: 10.1007/s004210050670
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen kinetics and modelling of time to exhaustion whilst running at various velocities at maximal oxygen uptake

Abstract: The purpose of this study was to characterise the relationship between running velocity and the time for which a subject can run at maximal oxygen uptake (VO2max), (tlimVO2max). Seven physical education students ran in an incremental test (3-min stages) to determine VO2max and the minimal velocity at which it was elicited (vVO2max). They then performed four all-out running tests on a 200-m indoor track every 2 days in random order. The mean times to exhaustion tlim at 90%, 100%, 120% and 140% vVO2max were 13 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
69
1
25

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 34 publications
12
69
1
25
Order By: Relevance
“…It is well known, however, that VO 2 max is lower in cycling compared with a running exercise [6] and that the energy cost of running on a treadmill is not similar to running on a track [7,8]. Since this study was performed 10 years ago [5], technological progresses have made it possible to measure all the factors in field experiments by using breath-by-breath portable oxygen analyzers [8][9][10][11][12][13]. Elite athletes, who generally are not available for testing in laboratory conditions, are often more open to field tests.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known, however, that VO 2 max is lower in cycling compared with a running exercise [6] and that the energy cost of running on a treadmill is not similar to running on a track [7,8]. Since this study was performed 10 years ago [5], technological progresses have made it possible to measure all the factors in field experiments by using breath-by-breath portable oxygen analyzers [8][9][10][11][12][13]. Elite athletes, who generally are not available for testing in laboratory conditions, are often more open to field tests.…”
Section: Introductionmentioning
confidence: 99%
“…Billat et al (2000) found that V max3par was not different from the maximum speed obtained in 20 m at maximal effort. However, Bosquet et al (2006) suggest that V max3par is smaller than the real V max (obtained by the average speed of the last 10 m of a maximal 40 m effort).…”
Section: Maximum Instantaneous Velocitymentioning
confidence: 64%
“…This statement is controversial and difficult to investigate because of the low reliability of time to exhaustion obtained in constant intensity tests (variability of tlim) (Hinckson & Hopkins, 2005). The SS equivalent to the Severe intensity domain includes performances of approximately 2 to 60 minutes (VO 2max reaching the end of the exercise) with the performance of 400 m in front crawl, the maximum aerobic speed (MAS) and CV 2par lying within that domain Lavoie et al 1983;Lavoie & Leone 1988;Rodrigues 2000;Pelayo et al 2007;Billat et al 2000;Dekerle et al 2010).…”
Section: Severe Intensity Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…The ta-95%VO2max parameter meant that VO2max was occured. The t-VO2max parameter related to balance between ta-VO2max and t-exh parameters (Billat et al, 2000). The ta-95%VO2max parameter had negative correlation with t-VO2max…”
Section: Discussionmentioning
confidence: 89%